PENGARUH PEMBERIAN RANSUM BERBASIS LIMBAH KELAPA SAWIT FERMENTASI TERHADAP KONSUMSI ENERGI DAN ENERGI TERCERNA PADA SAPI PERANAKAN ONGOLE (PO) - Hesti Utari Dewi; Liman ,; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This research aims to determine the impact of fermented palm oil waste in the ration to the energy intake and digestible energy in cattle grade Ongole. The research was conducted in September-December 2015 in the Laboratory Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study uses a randomized block design consisted of three treatments and three replications. Grouping based on body weight is between 200-250 kg in group I, between 170-199 kg  in group II, and between 140-169 kg in group III. Ration treatment used are R0 = control diet (15% of rice straw, 22% of copra meal, 32% of cassava waste, 25% of fine bran,  4% of molasses, 1% of urea, and 1% of premix), R1 = dietary based palm oil waste without fermentation (15% of palm midrib and leaves, 355 of copra oil, 18% of cassava waste, 25% of fine bran, 4% of molasses, 2% of urea, and  1% of premix) and R2 = dietary based palm oil waste fermented (15% of palm midrib and leaves fermented , 35% of copra oil, 18% of cassava waste, 25% of fine bran, 4%of molasses, 2% of urea, and 1% of premix). The data obtained were tested by analysis of variance followed by Least Significant Difference Test if the value of analysis of variance showed real results. The results showed that: (1) awarding dietary based palm oil waste significant (P <0.05) on energy intake and digestible energy. (2) the highest value of energy intake and digestible energy is on R2 with the dietary based palm oil waste fermented. Keywords :Digestible Energy, Energy Intake, Palm Oil Waste